Seismic metamaterial surface for broadband Rayleigh waves attenuation - Weijia Yu; Linyun Zhou (Materials & Design, 2023)
Elastic metamaterials (EMMs) have been widely studied owing to their advantages in controlling the propagation of elastic waves. In the past decade, considerable efforts have been made to attenuate Rayleigh waves using EMMs. However, the complex nonlinear behaviour of soil renders the realisation of existing EMMs challenging in practical engineering. To overcome this limitation, we present a new seismic metamaterial surface (SMMS) to isolate Rayleigh waves over a broad frequency range of 3.2–19.2 Hz. First, we discuss the propagation velocity of Rayleigh waves in EMMs and determine a reasonable design range for the effective dynamic material properties of the SMMS for seismic surface wave attenuation. Then, we construct a unit cell and demonstrate that these properties, both in band gaps and negative bands, lie within this specified design range. The negative bands are initially introduced into Rayleigh wave mitigation. Finally, a new type of SMMS is presented and validated using numerical results and scaled experiments. The results show that the vertical deformation on the surface can be decreased by more than 96 %. The findings reported here open new avenues for protecting engineering structures from low-frequency seismic vibrations.